2015
DOI: 10.1016/j.ijbiomac.2015.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic studies of a novel acid protease from Aspergillus foetidus

Abstract: The kinetics of a thermostable extracellular acid protease produced by an Aspergillus foetidus strain was investigated at different pH, temperatures and substrate concentrations. The enzyme exhibited maximal activity at pH 5.0 and 55°C, and its irreversible deactivation was well described by first-order kinetics. When temperature was raised from 55 to 70°C, the deactivation rate constant increased from 0.018 to 5.06h(-1), while the half-life decreased from 37.6 to 0.13h. The results of activity collected at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 18 publications
6
54
3
3
Order By: Relevance
“…As is known, Ed* is directly related to the activation enthalpy of thermal denaturation (ΔHd*), which is the total amount of thermal energy required to denature the enzyme and is related to the number of noncovalent bonds broken during the denaturation process . The positive and large values of ΔHd* estimated for A. tamarii FFase (290.4–290.3 kJ mol −1 ) (Table ) are consistent with the fact that enzyme denaturation is an endothermic process and with its high thermostability.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…As is known, Ed* is directly related to the activation enthalpy of thermal denaturation (ΔHd*), which is the total amount of thermal energy required to denature the enzyme and is related to the number of noncovalent bonds broken during the denaturation process . The positive and large values of ΔHd* estimated for A. tamarii FFase (290.4–290.3 kJ mol −1 ) (Table ) are consistent with the fact that enzyme denaturation is an endothermic process and with its high thermostability.…”
Section: Resultssupporting
confidence: 65%
“…44 As is known, E * d is directly related to the activation enthalpy of thermal denaturation (ΔH * d ), which is the total amount of thermal energy required to denature the enzyme and is related to the number of noncovalent bonds broken during the denaturation process. [45][46][47] The positive and large values of ΔH * d estimated for A. tamarii FFase (290.4-290.3 kJ mol −1 ) ( Table 4) are consistent with the fact that enzyme denaturation is an endothermic process and with its high thermostability. It has been proposed that the absorbed thermal energy increases the structural fluctuation in the enzyme structure and thus weakens or disrupts noncovalent bonds that hold it together; therefore, higher values of E * d and ΔH * d indicate stronger intramolecular stabilizing forces and a less extended conformation.…”
Section: Kinetic and Thermodynamic Parameters Of Ffase Thermal Inacsupporting
confidence: 77%
“…4 and 5). This was similar to the rhizopuspepsin from Rhizopus oryzae NBRC 4749 [25] and acid protease from Aspergillus foetidus [34], but lower than that of rhizopuspepsins (60°C) from R. chinensis Saito [14] and R. oryzae MTCC 3690 [11]. Fig.…”
Section: Results and Disscusionsupporting
confidence: 62%
“…Abdel-Naby 2017described a lower E a of 17.31 kJ/mol for alkaline protease from Bacillus stearothermophilus. Souza et al (2015) also found E a (19.03 kJ/mol) for acid protease from Aspergillus foetidus lower than that described in this study. It can be observed that the proteases produced by different microorganisms have different E a values.…”
Section: Determination Of the Kinetic And Thermodynamic Parameters Ofcontrasting
confidence: 65%